Vibration Analysis Of Fused Deposition Modeling Printed Lattice Structures Cellular Material - Azmi, Muhamad Syafwan (2019)
This research presents a vibration analysis on the lattice structure material fabricated by utilizing fused deposition modeling (FDM) additive manufacturing (AM) for application as load-bearing lightweight body part in automated device. The work has been motivated by the need to explore the dynamic behaviour of the lattice structure material so that the real behaviour of the system, performance, suitability and limitations can be understood and which at the end can provide better safety of the structure in the real dynamic applications. This work has undertaken on clarifying issues related to weight and built quality of the manufactured lattice structure material samples prior to vibration testing. The four proposed topological designs namely simple cubic (SC), face centred cubic (FCC), body centred cubic (BCC) and body centred cubic with reinforced z pillars (BCCz) are evaluated based on these two criteria which are from manufacturability and weight practicality. Based on the selection process, it is found that the BCC topological design of the lattice structure is more acceptable and henceforth used to represent the vibrational response study of the lattice structure cellular material with different strut diameter sizes. The results show that the natural frequency of the lattice structure material can be greatly affected by the strut diameter sizes due to increase in stiffness as the strut diameter increases. In addition, the mathematical equation is also derived to calculate the total area moments of inertia of the lattice structure model and the validity of this developed model is shown through comparison of the results with experimental work of the three-point bending test. From the calculation of total area moment of inertia, it is found that the lattice structure model with the highest strut diameter size yield highest value of total area moment of inertia. The results show a good agreement between the theoretical model and experimental work. The investigation on various effects of damage existence including damage locations and damage extents to the natural frequency values of the lattice structure material are also examined. The damage in the lattice structure is represented by a damage parameter η which indicates the ratio of missing unit cells to the total unit cells of the intact lattice structure. It is found that the natural frequency values decrease with the increase of damage parameter η from ratio of 0.00 to 0.50. Meanwhile, the natural frequency values increase as the damage location became farthest from the clamped edge. This indicates that the effect of damage on the natural frequency values become smaller as the damage zone moves from the clamped edge boundary condition to the free end. This research provides a good information on the influence of the strut diameter design parameter as well as the effects of damage existence to the natural frequency values of the lattice structure material and it can be seen that the results could constitute a useful information for subsequent investigation into the development of the lattice structure in order to fulfil the demand on the lightweight and cost reduction of materials.